1994
DOI: 10.1080/09658219408251492
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and daily schemas at work

Abstract: This exploratory study examines how daily schemas for work activities influence retrospective memory. Twelve subjects were asked to describe their 'typical day' at work, and to recall their work activities of yesterday and of the same day a week ago. The number of basic activities occurring in each description was counted, and the number of basic activities occurring in the typical day description was viewed as an index of the degree of elaboration of the schema. There were three major findings. First, people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The tags allowed the identification of specific cases for the informants to discuss, both prompting more detailed accounts of these cases and mitigating against the tendency to produce an idealised description (cf. Eldridge, Barnard and Bekerian, 1994). The interviews were semi-structured, ensuring that common areas were covered with all interviewees, while allowing further exploration of topics as they emerged.…”
Section: Interviewsmentioning
confidence: 99%
“…The tags allowed the identification of specific cases for the informants to discuss, both prompting more detailed accounts of these cases and mitigating against the tendency to produce an idealised description (cf. Eldridge, Barnard and Bekerian, 1994). The interviews were semi-structured, ensuring that common areas were covered with all interviewees, while allowing further exploration of topics as they emerged.…”
Section: Interviewsmentioning
confidence: 99%
“…According to this representational framework, SECs provide a general structure/organization in memory for particular behaviors over relatively long periods (e.g., from minutes to hours). SECs are stored representations of sequential event knowledge and represent sequences of activities that have been described elsewhere as ''scripts'' or ''schemas'' (Eldridge, Barnard, & Bekerian, 1994;Casson, 1983;Schank & Abelson, 1977). Grafman (1999) proposes that event features (an SEC subcomponent) are localized in the left PFC and that there is category specificity in terms of localization of these SEC representations within the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by [21], psychologists found a tendency for people with highly elaborated daily schemas to recall more activities from last week better than people with poorly elaborated schemas. Therefore, memory-supporting tools may be able to assist people to associate things in order to elaborate and consolidate their memories, and which can facilitate retrieval by strengthening the links between memories and the cues that life logs systems can provide, and potentially enhancing their efficiency at performing various tasks.…”
Section: Discussionmentioning
confidence: 99%